Affection of Law: Fichte on the Place and Boundaries of Pure Ethics of the Imperative - Sudakov A. K. (Кантовский сборник, 2019)
In his popular 1806 lectures on religion Fichte considered five possible worldviews in the second of which, “the standpoint of legality”, one can readily recognise the ethics of law of the Stoical and Kantian type. Fichte stresses that in his youth he himself shared this worldview. However, he hastens to adduce a series of original arguments to show that this position is essentially incapable of delivering a pure and higher moral doctrine. I examine the substance of these critical arguments in the context of his later metaphysics. Fichte maintains that in the “second type” of worldview man himself feels and understands, respects and loves himself only as a subject of unconditional law, therefore the pathos and “affection of law” pervades all his assessments and motivations. This affects the impartiality of moral assessment if the requirements of the law are diverged from. The “man of law”, the Stoic and Kantian who is not conscious of direct violations of the law, can at most not despise himself, but he cannot, according to Fichte, positively respect himself: that would require surpassing the requirement of the law through action. Meanwhile the affection of the self-sufficient law conceals even this impossibility from such a person. Finally, I show that the ethics of the Stoical and Kantian type retains, according to Fichte’s diagnosis, a refined interest in preserving and indulging the sensual self and hence the idea of God as the warrantor of empirical happiness / bliss. Accordingly, the “overturn in the state of mind” sought by the Kantian himself implies “the highest act of freedom”, which is inaccessible to him and beyond which the perspective of the world as law is replaced for the subject by the perspective of the Kingdom of the Spirit in which the “selfhood” of each moral agent is practically overcome.